2008
DOI: 10.1063/1.2801344
|View full text |Cite
|
Sign up to set email alerts
|

An overview on TRIUMF’s developments on ion source for radioactive beams (invited)

Abstract: The ISAC facility at TRIUMF utilizes up to 100 microA from the 500 MeV H(-) cyclotron to produce the radioactive ion beam (RIB) using the isotopic separation on line method. The ISAC-I facility comprised the RIB production target stations, the mass separator, and the beam delivery to low energy area and to a room temperature linear accelerator composed of a four-rod radio frequency quadrupole and an interdigital H-type structure drift tube LINAC. ISAC-I linear accelerator can provide beam from A=3 to 30 amu wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The beam was ionized using the Forced Electron Beam Ion Arc Discharge (FEBIAD) source [19] and transported at an energy of 20 keV to the TITAN facility. Contamination in both beams was removed using a two-stage high resolving power dipolemagnet mass separator.…”
Section: Aamentioning
confidence: 99%
“…The beam was ionized using the Forced Electron Beam Ion Arc Discharge (FEBIAD) source [19] and transported at an energy of 20 keV to the TITAN facility. Contamination in both beams was removed using a two-stage high resolving power dipolemagnet mass separator.…”
Section: Aamentioning
confidence: 99%
“…More than 20 years after the first (off-line) in-source laser spectroscopy on radioisotopes by the Letokhov group [71] in Troitzk and the proposal to use it at ISOL facilities [72], ion sources based on resonance ionization spectroscopy are now very common at ISOL facilities and are used, for example at ISOLDE in more than 50% of the beam times. With the exception of Oak Ridge National Laboratory [73,74], all other ISOL facilities using laser ion sources were represented at LASER 2009 in Poznan and the following reports on the status and further development work were given: Bruce Marsh and Anna Sjödin [75] for ISOLDE at CERN, Jens Lassen [76] for ISAC at TRIUMF, Mikael Reponen and Iain Moore [77][78][79] for IGISOL at Jyväskylä and Yuri Kudryavtsev [80,81] for LISOL at Louvain-la-Neuve.…”
Section: Trends and Future Directionsmentioning
confidence: 99%
“…Another solution called laser ion source trap (LIST), a combination of a laser ion source with an ion trap, was proposed by Blaum et al [89] quite some time ago. In the meantime development work at Jyväskylä [90], Louvain-La-Neuve [91], Mainz [83,92], and TRIUMF [76] was performed. A breakthrough was achieved by the Leuven group as mentioned above by the experiments on Cu isotopes at the LISOL facility in Louvain-La-Neuve [44], where a combination of an IGISOL gas cell and a linear sextupole radiofrequency trap was shown to suppress the isobaric background very effectively.…”
Section: Trends and Future Directionsmentioning
confidence: 99%
“…20 F development was carried out on the metastable atomic state of the stable isotope 19 F, and the results extrapolated to 20 F. The results showed that a 20 F beam polarization of ∼15% should be achievable. A FEBIAD (forced electron beam induced arc discharge) on-line ion source [14] which can produce a 20 F + beam has since been installed, making possible the future measurement of the alignment term of 20 F.…”
Section: Polarizing Non-alkali-metal Beamsmentioning
confidence: 99%